Proposta de um índice de avaliação da satisfação do uso do transporte público do município de São Carlos por meio da adaptação do Customer Satisfaction Score - Silva, Fernando Medeiros e (Universidade Federal de São Carlos, 2022)
As the years go by, some kinds of services gain relevance, some of them lose and others stay the same. Although, one thing is clear: the industry is becoming even more competitive. This progress proceeds with the increase of this service’s quality, the growth of the public demand, and the customer experience, mainly. This last topic is becoming one of the most important competitive factors in the actual industry, where the client is the focus of the service delivery. It can be said as well for São Carlos’ public transportation. It’s required to understand the customers’ satisfaction in the variable components of the system to analyze if this service delivery meets the population’s needs. Knowing that the main goal of the current research is to understand the satisfaction of the São Carlos’ population with the city’s public transportation by applying a form based on the Customer Satisfaction Score (CSAT) metric. The understanding was measured by collecting the relevance of these variable components coupled with the satisfaction of each one for the interviewed customers. This crossing resulted in a final satisfaction index of São Carlos’ public urban transportation. The final result categorized the São Carlos’ public transportation customers’ satisfaction as “low unsatisfied”. The research’s structure allows it to be applied in other cities, but it’s recommended to review the components that compose the evaluation.
Proposal of an evaluation index of satisfaction of public transport use in São Carlos city through the adaptation of the Customer Satisfaction Score
Keywords: Transporte público; São Carlos; Satisfação do usuário; Fatores de qualidade; CSAT; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES